PENGEMBANGAN LKPD MATEMATIKA BERBASIS STRATEGI PROBLEM BASED LEARNING MATERI BILANGAN BULAT NEGATIF KELAS VI - Urmila Umardianti; Bistari Bistari; Siti Halidjah (Universitas Tanjungpura, 2021)
AbstractThis research aims to analyze the initial conditions, describe the level of validity and analyze the level of completeness of student's scores on the results of developing mathematics student worksheets based on problembased learning strategies on the operation material of addition and subtraction of negative integers in class VI SDN 71 West Pontianak. The research method used is research and development (RnD) by adapting the Thiagarajan 4D design development model. The data source of this research is the results of the validation of three validators, as well as the test results of students on a small and large scale. The data collection technique of this research is validator questionnaire, test questions for students, and documentation on the validation process, as well as documentation during the use of LKPD by students. The results showed that during the development process of LKPD Mathematics based on problem-based learning strategies, it had gone through 4 stages, namely the define stage, the design stage, the development stage, and the dissemination stage. The feasibility of the LKPD average percentage of the learning aspect (material) is 96% with very valid criteria, from the technical / appearance aspects of 97.6% with very valid criteria and from the aspect of suitability to the problem-based learning strategy of 98.6% with very valid criteria. The level of completeness on the small scale obtained an average percentage of 50% with good criteria and the large scale obtained an average percentage of completeness of 85% with good criteria.Keywords: Development, Problem Based Learning Strategies, Student Worksheet